Laparoscopic pancreaticoduodenectomy with major venous resection and reconstruction with repassed round ligament: a case report - Cai, Yunqiang (Ann Transl Med, 2018)
It is technical challenging to perform laparoscopic pancreaticoduodenectomy (LPD) with major venous resection. Herein, we reported the first case of LPD with major venous resection and reconstruction with repassed round ligament. Between November 2015 and January 2018, a total of 35 LPD with major venous resection were performed in our department; however, only one patient underwent LPD with major venous resection and reconstruction with repassed round ligament. The patient suffered from pancreatic ductal adenocarcinoma with superior mesenteric vein and portal vein (SMV/PV) involvement. The operative time was 450 min and intra-operative blood loss was 200 mL. The duration of blood occlusion time was 48 min. No blood transfusion was required. The post-operative pathological examination showed that the pancreatic mass was pancreatic duct adenocarcinoma, and all the margins were negative. The post-operative period was uneventful. The patient was discharged on postoperative day 15. It is safe and feasible to perform LPD with major venous resection and reconstruction with repassed round ligament. However, long-term patency of repassed round ligament for venous reconstruction required further investigation.